2021
DOI: 10.48550/arxiv.2107.06680
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two-Dimensional Supersolid Formation in Dipolar Condensates

Thomas Bland,
Elena Poli,
Claudia Politi
et al.

Abstract: Dipolar condensates have recently been coaxed into supersolid phases supporting both superfluid and crystal excitations. While one-dimensional (1D) supersolids may be prepared via a roton instability, we find that such a procedure in two dimensions (2D) leads to greater heating. We go on to show that 2D roton modes have little in common with the supersolid configuration: instead, unstable centralized rotons trigger a process of nonlinear crystal growth. By evaporatively cooling directly into the supersolid pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…By varying the applied magnetic field in the vicinity of Feshbach resonances near 18-23 G, we can access scattering lengths that correspond to either unmodulated BECs or modulated states. In past works, we have demonstrated that modulated states created at the corresponding field have global phase coherence [23,24]. In this work, we expect the same to be true, but refer to these experimental states simply as modulated, as we do not repeat the characterization for every trap condition used.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…By varying the applied magnetic field in the vicinity of Feshbach resonances near 18-23 G, we can access scattering lengths that correspond to either unmodulated BECs or modulated states. In past works, we have demonstrated that modulated states created at the corresponding field have global phase coherence [23,24]. In this work, we expect the same to be true, but refer to these experimental states simply as modulated, as we do not repeat the characterization for every trap condition used.…”
mentioning
confidence: 86%
“…In the present work, we study the angular response of recently demonstrated supersolids with two-dimensional structure [23,24]. With this more favorable geometry, one may expect to observe unambiguous effects of superfluidity on the frequency of oscillations following a sudden angular rotation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While almost all dipolar supersolids have been experimentally realized as one-dimensional (1D) droplet arrays-see, for example, Refs. [10][11][12][13][14][15]-two recent experiments have for the first time created two-dimensional (2D) supersolids [29,30], thus opening an exciting frontier. An early theoretical study in 2D predicted a rich phase diagram determined by competing metastable crystal configurations [31].…”
Section: Introductionmentioning
confidence: 99%
“…So, it is not clear whether in one-row dipolar supersolids one can observe continuous, discontinuous or both types of quantum phase transitions, nor how these transitions relate to the general theory. For trapped supersolids with 2D lattice structures, numerical simulations predict discontinuous transitions [23,24].…”
Section: Introductionmentioning
confidence: 99%